Efek perceived value dan kualitas layanan terhadap behavioral intention: peran mediasi kepuasan pelanggan - Kiki Intan Sari; Hari Purwanto; Liliek Nur Sulistiyowati (MBR (Management and Business Review), 2022)
The purpose of this study was to determine the effect of perceived value and service quality on behavioral intention, and the role of mediation with satisfaction. Using a quantitative research approach, the research sample was 384 Indihome customers. The questionnaire was prepared using a 5-point Likert Scale, the data were analyzed by Path Analysis. The research findings explain that perceived value has an effect on service quality, behavioral intention, and customer satisfaction. Customer satisfaction mediates the effect of perceived value and service quality on behavioral intention. For further researchers, it is possible to enter the marketing mix variable.